Representation of self and other in "Arabian Sands" by Wilfred Thesiger: A study of travel literature - Shabira, Jasmina Hanan; Kurniawati, Novi (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2023)
Arabian Sands tells of a man from England who was born in Ethiopia and then explored the Arabian Desert called Rub Al Khali. This book is a travel writing based on the author's experience. In the book, the writer's sense of superiority and great respect for the Beduin, tribe who has long occupied Rub Al Khali is described. When viewed from the study of travel literature, this matter can be said to self and other representations. Therefore, this article will look at how the author describes self and others in the context of travel literature. The material object in this study is the book, Arabian Sands, while the formal object of this research is the representation of self and others in the perspective of Carl Thompson's travel writing. This research uses a descriptive-analytic research method. The results of the analysis of this novel show that there is a distance between the self and others that the author raises. In other words, even though the writer describes others positively, indirectly the writer has also described his position as self which is different from the place, culture, and people he meets in his travels. Apart from that, the writer also positions himself as other than his culture as Western because of the adaptations made to the eastern regions he visited. Thus, this novel shows the existence of dualism in representing self and other.